DEVELOPMENT OF FO/MD MODULE FOR PRODUCED WATER TREATMENT - ANANTH, GANESWARAN (IRC, 2019)
Forward osmosis (FO) can be used as either standalone or hybrid unit. The hybrid unit is required for recovery of draw solution. In many cases, the draw solution recovery consumed. Distilled water has been stimulated in this experiment in place of Produced Water. Membrane technologies have been actualized for treatment of PW as a result of its viability in expelling finely scattered oil droplets yet uses of pressure driven membrane forms seriously experience effects of layer fouling makes applications of independent forward osmosis (FO) and membrane distillation (MD). Be that as it may, the previous experiences a low flux and high energy for draw solute recuperation; the latter experiences membrane fouling. Along these lines, a novel FO/MD hybrid module is proposed in this venture to upgrade the capability of both FO and MD by facilitating mutual hybridization. This can be proven with FO-MD result where forward osmosis the flux started at 40 L/m2h eventually reduced to 19.2 L/m2h. In another side, membrane distillation flux, as time increases the flux increases at the end flux remain same at point where flux of 19.2 L/m2h. The interception point of FO and MD flux indicates there is possibility of FO-MD in one integrated module.